Oral microbial diversity analysis of caries-free and caries-active healthy Filipino adults through 16S Ribosomal RNA gene - Reyes, Candids Patrice A.
The oral cavity is inhabited by hundreds of bacterial species that play vital roles in maintaining oral health or in shifting to a diseased state like dental caries. These microorganisms have been studied using culture-dependent methods in the past. However, due to the limitations that are posted by microbial identification through culture techniques, molecular techniques are currently being utilized to better understand the bacterial etiology of dental caries. This study identified the various oral bacteria present in the saliva, plaque and carious enamel and dentin of caries-free and caries-active healthy Filipino adults using the 16S rRNA gene (16S rDNA). Bacterial DNA from the samples were amplified using polymerase chain reaction, diversity of the samples were assessed using denaturing gradient gel electrophoresis and the microorganisms were identified through sequencing of the 16S rDNA. Based on the gathered data, the caries-free group exhibited a more diverse microflora compared with their caries-active counterpart. Several bacteria were found to be common to both groups comprising the resident microflora. Lactobacillus plantarum, Neisseria subflava and Capnocytophaga species are some of the identified potentially cariogenic bacteria since they were seen only among the caries-active adults. The partial clone library of the 16S rDNA included various species of Leptotrichia, Streptococcus and Neisseria. This study provided baseline data on the microbial diversity profile of caries-free and caries-active Filipino adults using culture-independent techniques. This can assist researchers and dental practitioners to gain better understanding of the microbial etiology of dental caries. It may also be used in future caries risk assessment and anti-caries vaccine development.